Johor 300 early postcards - Cheah, Jin Seng (Editions Didier Millet, 2016)
Johor: 300 Early Postcards will present a series of postcard galleries showing various aspects of the Peninsular Malaysian state of Johor from the late 19th century to the mid-20th century, in particular the changing landscapes and townscapes. The book will be a richly informative visual guide to a formative period in Johor's history. The postcards presented in the book will be drawn from the vast postcard collection of Dr Cheah Jin Seng, the author of Malaya: 500 Early Postcards, Penang: 500 Early Postcards, Perak: 300 Early Postcards, Selangor: 300 Early Postcards and Singapore: 500 Early Postcards.